Association analysis of tolerance to dieback phenomena and trunk form using ISSR markers in Quercus brantii - Shamari, Abdol-Reza; Mehrabi, Ali-Ashraf; Maleki, Abbas; Rostami, Ali (Cellular and Molecular Biology, 2018)
Oak decline is a complex syndrome in which several damaging agents interact and bring about a serious dieback in tree condition. Genetic diversity is a key factor for better adoption of natural populations to environmental stresses. The objective of this research was to identify the association of polymorphism patterns of different reproducible genomic Inter simple sequence repeats (ISSR markers) to level of dieback phenomena and also growth type in 18 different stands of Persian oak in central Zagros region. Totally, 180 trees were sampled and evaluated for growth type, tree diameter at breast height (DBH) and level of tree dieback. Genomic DNAs extracted of fresh leaves amplified using 15 multi-locus ISSR primers. The population structure determined using the Bayesian model-based clustering method implemented in STRUCTURE software by Monte Carlo Markov Chain (MCMC) method. Five distinct sub-populations (K=5) determined by the log likelihood of the data. Genome wide association study (GWAS) performed using the generalized linear model (GLM) and the mixed linear model (MLM) with Kinship matrix. Informative alleles recognized for level of tolerance to dieback and tree growth type traits. It was observed a significant co-segregation for phenotypic data and some of amplified fragments. Identification of these informative DNA markers can be utilized for pre-screening of high quality oak seedlings in early growth stages and better management in restoration of damaged stands.